Exploring non-price factors shaping supply response: insights from Cameroon's banana and pineapple horticultural industries - Awa, Samuel Taka; Molua, Ernest; Raoul Fani, Djomo Choumbou; Tabetando, Rayner; Nkendah, Robert; Ndip, Francis E. (Frontiers in Environmental Economics, 2024)
Horticulture has the potential to meet the development agenda of agrarian economies, like that of Cameroon, through the cultivation of high-value fruits and vegetables. Bananas and pineapples are two widely grown fruits in Cameroon for income, employment, and foreign earnings.Cameroon remains an important global player in the banana trade. To boost production, identifying important factors that drive the supply response of such crops is an important policy question. Here, we ask if non-price factors are important determinants of supply response of such horticultural crops, a question that has received very little attention. The objective of this study is thus to estimate the effect of non-price factors on the supply response of bananas and pineapples.To do this, a Nerlovian response function is directly estimated via an Error correction model using time series data, to capture long-run dynamics of production and supply. The results show that non-price factors such as rainfall, temperature, and land are the major drivers of the supply response of both crops. The effects of these factors, however, vary with the crops. We provide plausible explanations why non-price factors are salient. Our results suggest that improving the timely availability of weather and climate information, and input subsidies are possible areas for policy interventions.